(untitled) (Journal of the College of Basic Education, 2023)
The research aims to know (the effect of the voting points strategy on the achievement of Arabic grammar for sixth graders of primary school), and the researcher chose his research community in the province of Baghdad, and a sample of sixth-grade primary students intentionally from (Al-Manhal Primary School for Boys) affiliated to the Baghdad Directorate of Education Rusafa The third for the academic year (2019-2020), the research sample amounted to (40) students who were randomly distributed into two groups, the first (20) experimental students who were studied using the (voting points strategy), and the other (20) control students who were taught in the traditional way. The researcher was rewarded with the following variables: (chronological age calculated in months, parents’ academic achievement, previous year’s grades, and intelligence test). The researcher formulated (58) behavioral goals, prepared teaching plans, and chose a topic from the curriculum to be taught; To represent the achievement measurement tool, the researcher prepared an achievement test for the students of the two groups consisting of (49) items from a variety of multiple-choice. The researcher applied the achievement test to the students of the two groups at the end of the experiment, and used the appropriate statistical means in his research, and the results showed that the students of the experimental group who studied using the (voting points strategy) outperformed the students of the control group who studied in the traditional way in the achievement test. The researcher recommended the adoption of the (voting points strategy) in teaching grammar to sixth graders; As one of the modern strategies that provide an opportunity for reflection, reflection, and dialogue among learners, in the classroom. The researcher suggested conducting similar studies to search for other (variables such as reflective thinking and critical thinking). More about this source textSource text required for additional translation information Send feedback.